The Effects of Auditor Tenure on Fraud and Its Detection - Patterson, Evelyn R.; Smith, J. Reed; Tiras, Samuel L. (The Accounting Review, 2019)
ABSTRACT We examine the strategic effects of auditor tenure on the auditor's testing strategy and the manager's inclination to commit fraud. Most empirical studies conclude that longer tenure improves audit quality. Proponents of restricting tenure argue that longer tenure impairs auditor independence and a “fresh look” from a new auditor results in higher audit quality. Validating this argument requires testing whether the observed difference in audit quality between a continuing auditor and a change in auditors is less than the theoretically expected difference in audit quality without impairment. Our findings provide the guidance necessary for developing such tests. Our results show that audit risk (the probability that fraud exists and goes undetected) is lower in both periods for the continuing auditor than with a change in auditors. More importantly, we show that across both periods, expected undetected fraud is lower for the continuing auditor than with a change in auditors.